In vivo classification of two closely related species of mice, mound-building mouse (Mus spicilegus) and house mouse (Mus musculus) - Bárdos, Boróka; Kovács, Bianka; István, Nagy; Altbäcker Vilmos (Acta Agraria Kaposváriensis, 2022)
Correct identification of similar, closely related species with overlapping distribution is a crucial point in field biology. In small mammal studies, species identification is particularly problematic in population studies using trapping where live animals need to be identified. The aim of our research was to develop a method making the classification of the two Hungarian mouse species, mound-building mouse (Mus spicilegus) and house mouse (Mus musculus) possible based on morphometric characters. The basis to obtain reference data was the captive populations of caged animals housed in our laboratory where the true species classification was known for every animal. Body weight, body length, tail length, and tail diameter were measured for 56-56 individuals from both species. From these measurements the ratio of the body length/tail length was also calculated. Besides, the sex and age of these animals were also recorded. Data analysis consisted of stepwise discriminant procedure and discriminant analysis, respectively. The stepwise discriminant procedure restricted the morphometric characters to the ratio of the body length/tail length and tail diameter. Performing the discriminant analysis to these body measures a perfect classification was obtained even using cross-validation. Thus, applying the obtained discriminant function to the classification of any live trapped mice is feasible.